Effects of illumination on electrical parameters of Ag/n-CdO/p-Si diode - Karatas, Sukru; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2013)
The current-voltage (I-V) characteristics of the Ag/n-CdO/p-Si diode were investigated under various white light (visible light) illuminations. The electrical parameters such as ideality factor (n), zero-bias-barrier height (Phi(b)) and series resistance (R-s) of Ag/n-CdO/p-Si MIS diodes were determined by using the forward bias current-voltage measurements. The Ag/n-CdO/p-Si diode exhibits a non-ideal behavior due to the interfacial layer, the interface states and the series resistance. The ideality factor is increased, while the barrier height is decreased with decreasing illumination intensities. The values of Rs obtained from Cheung and Norde methods are decreased with increasing illumination intensity. The distribution profile of the interface states (N-SS) as a function of energy distribution (E-SS - E-V) was extracted from the forward I-V measurements under various illumination intensities. The interface state densities were observed to be strongly illumination dependent and are decreased with increasing illumination intensities. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Oxides; Interfaces; Sol-gel growth; Heterostructures